Adsorption properties of ZrO2 hollow microboxes prepared using CaCO3 cubes as templates. Issue 85 (30th August 2016) - Zhu, Weixue; Ge, Shengsong; Shao, Qian
Abstract : ZrO2 hollow microboxes prepared using CaCO3 cube as template exhibit excellent dye adsorption performance from wastewater. Abstract : Zirconia hollow microboxes were prepared using calcium carbonate cubes as templates. The as-prepared products were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM) and nitrogen adsorption–desorption isotherms. Adsorption performance of the as-prepared products toward Congo red (CR) aqueous solutions was tested and discussed. Results show that ZrO2 hollow microboxes copied the morphology of the CaCO3 template very well with a diameter of ∼1.5 μm and a possible formation mechanism was proposed according to the observed results. The Langmuir surface area and BET specific surface area of ZrO2 hollow microboxes before calcination are 301.65 m 2 g −1, 247.88 m 2 g −1, respectively and the maximum adsorbance was found to be 188.02 mg g −1 which is much higher than that of ZrO2 hollow microboxes after calcination (90.86 mg g −1 ) and ZrO2 nanoparticles (57.86 mg g −1 ). The adsorption kinetics and isotherms can be well described by the pseudo-second order rate model and Langmuir equation, respectively. These results indicate that ZrO2 hollow microboxes before calcination have great potential in removing dyes from a water environment.